Quarter life crisis in the communication process on early adulthood - Novi Andayani Praptiningsih; Silvie Mil; Herri Mulyono; Joseph Agbuya Villarama; Ninez B Tulo; Nerissa S Olarte (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the phenomenon of Quarter Life Crisis (QLC) in emerging adults. The research was conducted using a qualitative approach through in-depth interviews with several informants and analysis of relevant literature. The findings indicate that Quarter Life Crisis is a condition commonly experienced by individuals during the transition from late adolescence to early adulthood. Common symptoms include anxiety about the future, confusion in making major life decisions (such as choosing between continuing education or getting married), social pressure, and frustration due to social comparison with peers. The main contributing factors to QLC include intolerance to uncertainty, suboptimal personal growth, and low family functioning. Using a holistic-systemic model, the QLC experiences of each informant in this study are understood as a process of communication with the surrounding environment and self-transformation, through four phases: locked-in, separation, exploration, and rebuilding.